Fabrication of B doped g-C3N4/TiO2 heterojunction for efficient photoelectrochemical water oxidation. (20th August 2018) - Kong, Weiqian; Zhang, Xiaofan; Chang, Binbin; Zhou, Yannan; Zhang, Shouren; He, Guangli; Yang, Baocheng; Li, Junjie
Abstract: With the development of clean and renewable energy, hydrogen produced via photoelectrochemical (PEC) water splitting has attracted considerable attention. However, to develop the photoanodes with stable and excellent PEC ability is still a big challenge. In our work, TiO2 nanorods decorated with boron doped g-C3 N4 (BCN/TiO2 ) is fabricated via thermal polymerization method to improve the PEC performance. The BCN/TiO2 displays 4-fold increase of the photocurrent density (1.01 mA cm −2 ) at 1.23 V vs. RHE under irradiation (100 mW cm −2, AM 1.5 G). And the onset potential of BCN/TiO2 exhibits a negative shift with 100 mV. Attributed to the broad light absorption of BCN and hetero-junction forming between BCN and TiO2, the IPCE value is increased to 87.8% in 380 nm, and the charge separation and transfer efficiency are both increased. Doping metal-free inorganic material with heteroatoms is a simple and efficient strategy to increase the light absorption within visible light and charge transfer efficiency in PEC and photocatalytic applications. Graphical abstract: Image 1 Highlights: BCN/TiO2 hetero-junction is fabricated via in-situ thermal polymerization method. A 4-fold increase of the photocurrent density is obtained for BCN/TiO2 . The onset potential of BCN/TiO2 exhibits a negative shift with 100 mV. Light absorption and charge separation/transfer process are improved for BCN/TiO2 .